Capturing RNA–protein interaction via CRUIS. Issue 9 (6th March 2020) - Zhang, Ziheng; Sun, Weiping; Shi, Tiezhu; Lu, Pengfei; Zhuang, Min; Liu, Ji-Long
Abstract: No RNA is completely naked from birth to death. RNAs function with and are regulated by a range of proteins that bind to them. Therefore, the development of innovative methods for studying RNA–protein interactions is very important. Here, we developed a new tool, the C RISPR-based RNA-United Interacting S ystem (CRUIS), which captures RNA–protein interactions in living cells by combining the power of CRISPR and PUP-IT, a novel proximity targeting system. In CRUIS, dCas13a is used as a tracker to target specific RNAs, while proximity enzyme PafA is fused to dCas13a to label the surrounding RNA-binding proteins, which are then identified by mass spectrometry. To identify the efficiency of CRUIS, we employed NORAD (Noncoding RNA activated by DNA damage) as a target, and the results show that a similar interactome profile of NORAD can be obtained as by using CLIP (crosslinking and immunoprecipitation)-based methods. Importantly, several novel NORAD RNA-binding proteins were also identified by CRUIS. The use of CRUIS facilitates the study of RNA–protein interactions in their natural environment, and provides new insights into RNA biology.